Political corruption in contemporary democracies: Newness, scale and varieties - Richard Rousseau (IBSU Scientific Journal (IBSUSJ), 2008)
A rise in corruption and in the exposure of corruption in recent decades is observable in contemporary democracies, especially on the European continent. Anti-corruption campaigns on the part of magistrates and others have increased in the past two decades, and as a consequence revelations about corruption have become more widespread. This has not just been at national level, but at the supranational and international levels, e.g. the EU. This article exposes this phenomenon in democratic countries and examines the possible remedies and solution adapted to highly develop societies.
Keywords: 330; developed countries; democracy; corruption; solutions